Overseas Media and the Rebuilding of West Sumatra: A Preliminary Study of Aneka Minang 1972-1973 - Israr, Israr (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The role and existence of the mass media, especially the print media, in the process and efforts to restore and rebuild the West Sumatra region in the early days of the New Order was very important. The mass media in question are not only those that exist in West Sumatra, but also those published in overseas areas. Among the mass media published and managed by the diaspora (migrants) from Minangkabau is Aneka Minang magazine. This ethnic Minangkabau magazine published in Jakarta is not only circulated in overseas areas, especially Java, but also in West Sumatra itself. By using historical research methods, namely heuristics (source collection), criticism (external and internal), interpretation and historiography (historical writing). The research results reveal the significant role of Aneka Minang magazine as a mass media of Minangkabau people published in overseas areas in assisting the recovery and rebuilding program of West Sumatra after being devastated by the political upheaval of the Revolutionary Government of the Republic of Indonesia (PRRI) and the turbulent transition between the Old Order (Guided Democracy) regime to the New Order in the region.